Sosialisasi Tentang Alat Pelindung Diri kepada Pekerja Proses Pengolahan Minyak Kelapa Sawit PT. PAA - Asrawi, Asrawi; Rahayu, Endang Purnawati; Tampubolon, Harlen (Penerbit Goodwood, 2024)
Purpose: This community service is carried out with the aim of increasing workers' knowledge about personal protective equipment and increasing awareness about the use of personal protective equipment so that it can protect workers from work accidents. Community service activities are carried out at PT. PAA Bengkalis Regency from 27 November to 14 December 2023. Methodology: The stages of implementing community service activities begin with a pretest, to measure the participants' abilities and understanding. about knowledge of personal protective equipment (APD). Furthermore, several interventions were carried out, including outreach aimed at increasing workers' understanding and awareness about PPE. At the end of the program, a post test is carried out to determine the level of success in implementing service to workers. Results: The results of the evaluation of the implementation of community service activities through pre-test and post-test show an increase in workers' understanding and concern for personal protective equipment (PPE). Limitation: The limitations of this service are ongoing monitoring and evaluation which is not carried out directly by researchers, but by HSE officers. Contribution: in this research is in the form of attitude change based on in-depth understanding. so that this effort allows attitudes and actions based on understanding to continuously. The limitations of this service are ongoing monitoring and evaluation which is not carried out directly by researchers, but by HSE officers.